2011
DOI: 10.4056/sigs.1503846
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Paludibacter propionicigenes type strain (WB4T)

Abstract: Paludibacter propionicigenes Ueki et al. 2006 is the type species of the genus Paludibacter, which belongs to the family Porphyromonadaceae. The species is of interest because of the position it occupies in the tree of life where it can be found in close proximity to members of the genus Dysgonomonas. This is the first completed genome sequence of a member of the genus Paludibacter and the third sequence from the family Porphyromonadaceae. The 3,685,504 bp long genome with its 3,054 protein-coding and 64 RNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…1 ). This separation has also been demonstrated previously using analysis of 16S rDNA gene sequences ( Fournier et al 2001 ; Summanen et al 2009 , 2005 ; Gronow et al 2011 ). The nonoral isolates (isolated from a skin abscess, leg ulcer, and bovine rumen) have been described as opportunistic pathogens, with their presence reported in clinical infections in a number of studies ( Finegold et al 2004 ; Summanen et al 2005 ; Sweeney et al 2009 ).…”
Section: Discussionsupporting
confidence: 80%
“…1 ). This separation has also been demonstrated previously using analysis of 16S rDNA gene sequences ( Fournier et al 2001 ; Summanen et al 2009 , 2005 ; Gronow et al 2011 ). The nonoral isolates (isolated from a skin abscess, leg ulcer, and bovine rumen) have been described as opportunistic pathogens, with their presence reported in clinical infections in a number of studies ( Finegold et al 2004 ; Summanen et al 2005 ; Sweeney et al 2009 ).…”
Section: Discussionsupporting
confidence: 80%
“…One gene designated as cpheE1 was always present and encodes a canonical single domain cyanophycinase. The other gene ( cphE2 ), which was missing in the genome of Paludibacter propionicigenes DSM 17365 T (Gronow et al ., ), contains an additional C‐terminal region that seems to have a function in the transport and anchoring of the protein to the outer membrane (in most cases a Por secretion system domain). Interestingly, in several cases the cyanophycinase domain of the cphE2 gene was highly divergent to typical cyanophycinases, which could indicate a relaxed selection pressure on the enzymatic function of the CphE2 protein.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the likely location of nitrogen fixation, nitrogenase gene expression was quantified by using nifH-qPCR. This demonstrated that nifH expression was highest in the AHG (27-fold higher than the FG; Table 2), with the predominant nifH transcript sequences related to the Ni-Fe nitrogenase of the member of the Porphyromonadales, P. propionicigenes (Gronow et al, 2011) as well as the Ni-Fe nitrogenase of Clostridiales member, C. lentocellum, a cellulolytic N 2 -fixing bacterium (Leschine and Canale-Parola, 1989;Leschine, 1995). NifH expression results confirmed our hypothesis of microbial compositional and functional segregation because of differential physiological conditions, that is, variation in O 2 concentrations at each gut region.…”
Section: Discussionmentioning
confidence: 99%